Deconvoluting lung evolution: from phenotypes to gene regulatory networks - Torday, John S. (Oxford University Press, 2007)
Speakers in this symposium presented examples of respiratory regulation that broadly illustrate principles of evolution from whole organ to genes. The swim bladder and lungs of aquatic and terrestrial organisms arose independently from a common primordial “respiratory pharynx” but not from each other. Pathways of lung evolution are similar between crocodiles and birds but a low compliance of mammalian lung may have driven the development of the diaphragm to permit lung inflation during inspiration. To meet the high oxygen demands of flight, bird lungs have evolved separate gas exchange and pump components to achieve unidirectional ventilation and minimize dead space. The process of “screening” (removal of oxygen from inspired air prior to entering the terminal units) reduces effective alveolar oxygen tension and potentially explains why nonathletic large mammals possess greater pulmonary diffusing capacities than required by their oxygen consumption. The “primitive” central admixture of oxygenated and deoxygenated blood in the incompletely divided reptilian heart is actually co-regulated with other autonomic cardiopulmonary responses to provide flexible control of arterial oxygen tension independent of ventilation as well as a unique mechanism for adjusting metabolic rate. Some of the most ancient oxygen-sensing molecules, i.e., hypoxia-inducible factor-1alpha and erythropoietin, are up-regulated during mammalian lung development and growth under apparently normoxic conditions, suggesting functional evolution. Normal alveolarization requires pleiotropic growth factors acting via highly conserved cell–cell signal transduction, e.g., parathyroid hormone-related protein transducing at least partly through the Wingless/int pathway. The latter regulates morphogenesis from nematode to mammal. If there is commonality among these diverse respiratory processes, it is that all levels of organization, from molecular signaling to structure to function, co-evolve progressively, and optimize an existing gas-exchange framework.